Deceitful consent: decoding some aspects of African space in Doris Lessing's fiction and non-fiction - Šesnić, Jelena (Array, 2004)
Doris Lessing's opus, initially positioned on the "margins of empire", has undergone in recent years a kind of "centering" within the expanding order of English/commonwealth literature. Here attention will be given to her "African corpus", as a body of text which combines startling insights into the workings of spatial economies, institutional and social coercions (ranging from the apparatuses of colonial society to those of literature), and the ways they have marked the trajectories traversed by the colonial and the colonized subjects, including here also Lessing and her family. The aim of this article is to demonstrate how such change of critical focus may affect the assessment of strategies in her fictional and auto-biographical discourses that specifically deal with Southern Africa. The inquiry will be refracted through questions posed at the intersections among spatiality theories, masculinity studies, feminist and postcolonial criticism.